Complementary oncology: adjunctive methods in the treatment of cancer - Beuth, Josef; Moss, Ralph W.; Abel, Ulrich (Thieme, 2010)
Complementary methods are playing an increasingly important role in these treatment of cancer. Resulting benefits are a higher quality of life, reduced instance and